2014
DOI: 10.3126/ijasbt.v2i2.10352
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Analysis and Microbial Diversity of Yamuna Water and Industrial Effluents

Abstract: Pollution has arisen as a serious environmental concern to the present world after industrialization of human societies. It has severely affected our air, soil and water sources. Looking to its global, national, regional and local dimensions, it is now imperative to check it at each and every level. In the present study, 8 samples (3 Yamuna water samples, 3 tannery effluent samples and 2 textile effluent samples), were collected from different sites of Yamuna and exit points of textile and tannery Industries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The value of pH, Total Hardness, B.O.D, D.O, and MPN were Compared to Standard of B.I.S [11] . A similar study was carried out by Gupta et al [10] on river Yamuna and they reported high value of total hardness, B.O.D and Lower D.O level than the standard limits.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…The value of pH, Total Hardness, B.O.D, D.O, and MPN were Compared to Standard of B.I.S [11] . A similar study was carried out by Gupta et al [10] on river Yamuna and they reported high value of total hardness, B.O.D and Lower D.O level than the standard limits.…”
Section: Resultssupporting
confidence: 68%
“…There is no any major industrial setup present along these 16 ghats. Industrial effluents contain cations (calcium, magnesium and sodium) which increase total hardness [10] . Absence of industry along above the ghats keeps hardness levels lower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, risks of pollution of water and air have been highly increased. Previously, textile effluents have been considered as the most polluting among all in the industrial sectors by volume and composition of effluent [ 1 3 ]. Typically, textile effluents is characterized by high values of BOD, COD, color and pH [ 4 – 5 ].…”
Section: Introductionmentioning
confidence: 99%